Dampak Subsidi Pendidikan BOS dan KIP Pada Pengeluaran Rumah Tangga Miskin dan Rumah Tangga non Miskin di Wilayah Bandung Timur - Yuanisa Mulia Hendriyani; H.R.Abdul Maqin (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to determine and analyze the impact of the education subsidy program on household expenditures for the poor and non-poor households in Babakan Sari Village, Kiaracondong District, East Bandung. The aspects analyzed are differences in people's income, food and non-food expenditures, education subsidies, education expenditures, and education subsidies to food and non-food expenditures, in the poor and non-poor communities. This study uses a primary quantitative data analysis method, from the data processing shows that there are differences in the results of expenditures for poor households with non-poor household expenditures. Through this research, it is hoped that the poor can improve the quality of their education because education has a very important role in the development of a country. For non-poor people, they should care about education by provide financial assistance to schools for the advancement of education.